Phytochemicals and Antimicrobial Analysis of Ixora Coccinea Flower Extract - J, Gani; I, Nkafamiya I.; A, Akinterinwa (Darul Yasin Al Sys, 2024)
Ixora coccinea, also known as jungle geranium, is a flowering plant from the Rubiaceae family. It is a tiny, bushy shrub that produces beautiful scarlet flowers and is commonly grown for its ornamental qualities. In addition to its visual appeal, Ixora coccinea has long been employed in a variety of therapeutic traditions due to its potential health advantages. The aim of this work was to conduct phytochemical screening and antimicrobial analysis on a methanolic extract of the flower of Ixora Coccinea. Phytochemicals are plant-derived bioactive molecules that have been proved to offer a variety of health benefits. The phytochemical screening of the methanolic extract identified alkaloids, glycosides, proteins, tannins, saponins, phenols, terpenoids, and steroids while flavonoids was absent. The antimicrobial results of the investigation demonstrated that Ixora coccinea floral extract had strong antibacterial activity against a variety of pathogens. Minimum inhibitory concentration (MIC) values for the extract ranged from 25 % to 75 % while the minimum bactericidal concentration (MBC) values for active extract ranged from 15 to 37 mg/ml. The extract had inhibitory effects on both Gram-positive and Gram-negative bacteria, as well as fungal strains. These findings indicate that the phytochemicals found in Ixora coccinea have powerful antibacterial activities that could be used for medicinal purposes.